Criminological Review On The Impact Of The Abuse Of Alcoholic Beverages That Trigger Criminal Actions In The City Of Gorontalo - Putri Regina Titania Inggile (Estudiante Law Journal, 2023)
The purpose of this research is to discuss the impact of alcohol abuse that triggers criminal acts in the city of Gorontalo . The objectives of this research are: to find out what are the factors and impacts of alcohol abuse in Gorontalo City.This study uses empirical legal research methods. Empirical legal study itself is a study that views law as a reality, including social reality, cultural reality, and empirical studies of the world. This research took place at the Gorontalo City Police. The results obtained from this study are that the prevalence of alcohol abuse in Gorontalo City occurs due to internal factors such as age, gender, individual norms (personality), education, psychology and others, as well as external factors such as the environment and friendships. The influence of alcoholic beverages can lead to a crime.